The Gasing Method with the Traditional Game-Based Mong-Mongan Approach on the Mathematics Learning Outcomes of Third Grade Elementary School Students - Komang Ratna Sariningsih; Desak Putu Parmiti; I Kadek Edi Yudiana (Universitas Pendidikan Ganesha, 2025)
This study is motivated by the low mathematics learning outcomes among students and their difficulty in understanding fundamental mathematical concepts. The purpose of this research is to examine the effect of the Gasing method combined with the traditional number-based game mong-mongan on improving mathematics learning outcomes in elementary school students. A quasi-experimental design was employed, using a non-equivalent control group design. The research sample consisted of two third-grade classes selected purposively: one as the experimental group and the other as the control group. Data were collected through a mathematics achievement test and analyzed using an independent t-test. The results revealed a significant difference in learning outcomes between students taught using the Gasing method integrated with traditional games and those taught using conventional methods. The findings indicate that the Gasing method, when integrated with local cultural games, is more effective in enhancing students' mathematics achievement. These results highlight the importance of innovative, culturally responsive teaching strategies that provide meaningful and enjoyable learning experiences for students.